Detection of OXA-1 β-lactamase gene of Klebsiella pneumoniae from blood stream infections (BSI) by conventional PCR and in-silico analysis to understand the mechanism of OXA mediated resistance. - Madhan Sugumar (Public Library of Science (PLoS), 2014)
Klebsiella pneumoniae strains producing extended-spectrum β-lactamases (ESBL) exhibit resistance to antibiotic classes. The production of ESBLs (TEM-1, TEM-2, SHV-1, OXA-1) results in resistance to ampicillin, ticarcillin, piperacillin and cephalosporins. High levels of β-lactamases leads to development of resistance to β-lactamase inhibitors. The present study deals with characterizing antimicrobial resistance pattern among septicemia causing K. pneumoniae and the prevalence of inhibitor resistant OXA-1 β-lactamase genes among them. Of 151 study isolates, 59 were resistant to piperacillin/tazobactam and these isolates were further selected for blaOXA-1 screening. Amplification of β-lactamases genes by conventional PCR showed the presence of blaOXA-1 genes among 12 K. pneumoniae (20.3%) isolates. OXA-1 β-lactamase producing strains were found to be resistant to piperacillin/tazobactam(100%), levofloxacin (91.6%), amikacin (75%), cefoxitin (50%), ertapenem (25%), imipenem (16.6%) and meropenem (16.6%); all were susceptible to tigecycline. 3D models of OXA-1 β-lactamase were generated and docking was performed with various β-lactam antibiotics. Molecular docking (MD) revealed the molecular basis of drug sensitivity. MD simulation results clearly confirmed the notable loss in stability for tigecycline-blaOXA-1 complex. Findings of the present study will provide useful insights for understanding the mechanism of resistance and help with strategies for the development of new antibiotics. The conventional PCR assay designed in this study can be routinely used in clinical microbiology laboratories to determine the blaOXA-1 genes.